Effect of Al content on the selective leaching property of AlxCoCrFeNi high-entropy alloys. (August 2022) - Chang, Shih-Hang; Huang, Shih-Ping; Wu, Shyi-Kaan
Abstract: This study investigates the selective leaching behavior of Al0.2 CoCrFeNi, Al0.6 CoCrFeNi, and Al1 CoCrFeNi high-entropy alloys (HEAs) in a simulated body fluid environment to assess their potential long-term orthopedic implant applications. The concentrations of Al, Cr, and Fe ions released from the Alx CoCrFeNi HEA were relatively lower than those of the Co and Ni ions because Al, Cr, and Fe atoms are primarily in their oxidation states near the surface of the alloys. The selective leaching property of the Al0.2 CoCrFeNi HEA was slightly worse than that of the CoCrFeNi medium-entropy alloy because the porous and poorly protective Al2 O3 films formed on the surface of the Al0.2 CoCrFeNi HEA deplete the protection of the Cr2 O3 and Fe2 O3 passive films. Furthermore, the concentrations of the metal ions released from the Al0.6 CoCrFeNi and Al1 CoCrFeNi HEAs were much higher than those released from the Al0.2 CoCrFeNi HEA because their complicated BCC + FCC dual-phase structure facilitates the selective leaching rates of the ions. Alx CoCrFeNi HEAs with a fully single-phase structure were found to be suitable for biomaterials, whereas those with a dual-phase structure exhibited poor selective leaching properties and were found to be inadequate for long-term implant applications. Graphical Abstract: ga1